Home Leisure Wear Recommendation on Social Media: Theory of Planned Behaviour Applied - Nur Fitri Rahmawati; Anita Maulina; Rousdy Safari Tamba; Dewi Nurbaiti; Yoka Mai Patria (Budapest International Research and Critics University, 2021)
This research was conducted to see the consumer behavior of recommendation intention on social media to use home leisure wear with theory of planned behavior applied. This research can be a contribution for fashion industry and maximizing business strategies. The problem raised is how the attitude construct, subjective norm and perceived behavioral control influence intention to recommend home leisure wear on social media. The novelty of the research is intention to recommend using social media platforms and fashion products with home leisure wear specification. Structural Equation Modeling (SEM) was used to analyze the data obtained with the SmartPLS. Questionnaires in easy-to-understand language were distributed to 143 respondents who filled them out perfectly. There are three conclusions and two of them are rejected hypotheses. The subjective norm construct became the most influential construct in the intention to recommend home leisure wear. Further research is expected to take larger data, longer period and broaden the target characteristics of respondents.